Pelaksanaan PKK di Desa Suak Puntong Kecamatan Kuala Pesisir (Studi Kasus Pokja: Pendidikan dan Keterampilan) - Mirna Mirna; Nellis Mardhiah (Pencerah, 2022)
Family Welfare Empowerment (PKK) is a women-only social organization. The PKK was founded for the welfare of the family, because the family is the community that builds the nation. The purpose of this study is to explain and describe how family welfare empowerment activities (PKK) policies are implemented in work programs in the field of education and skills in Suak Puntong Village, Kuala Pesisir District, Nagan Raya Regency. The research method used was qualitative research with a case study approach. The findings of this study indicate that the existing Pokja II education and skills program, such as sewing training for the community, cooking training, making wedding delivery baskets, stringing Acehnese betel nut, arranging flowers, and other hand skills useful in people's daily lives, is being implemented quite well. This can be seen in the existing sewing, handicrafts, and cooking programs, but their implementation is not carried out properly due to a variety of obstacles, including the replacement of village heads every period with the person in charge (PJ), which results in policies that are not carried out optimally when implemented.